EFEKTIVITAS PELAYANAN PUBLIK DI KANTOR KECAMATAN TELLU LIMPOE KABUPATEN SIDENRENG RAPPANG - Muhammad Aswar (PRAJA: Jurnal Ilmiah Pemerintahan, 2017)
This study aims to determine the effectiveness of public services at the Tellu Limpoe District Office, Sidenreng Rappang Regency and to determine the factors that influence the effectiveness of public services at the Tellu Limpoe District Office, Sidenreng Rappang Regency. The population in this study were the people who received service from June to July 2015 at the Tellu Limpoe District Office as many as 50 people. Sampling was carried out using a total sample so as to produce a sample of 50 people. The data collection techniques carried out in this study were observation, questionnaires, interviews (interviews) and literature studies. The data collected is then used quantitative data analysis techniques with frequency tables. The results of this study indicate that the effectiveness of public services at the Tellu Limpoe District Office, Sidenreng Rappang Regency is categorized as good with an average number of 66.75% and the factors that affect the effectiveness of public services at the Tellu Limpoe District Office, Sidenreng Rappang Regency are categorized quite well with an average number 69% average.